Photometric calibration and out-of-focus blur compensation for projector camera systems - Song, Peng (2008)
In this thesis, a review of standard technical concepts in relation to projectors and cameras is provided. Recent approaches to geometric calibration are briefly discussed, and the standard geometric calibration method used in the thesis work is described. A novel framework for grayscale photometric calibration of overlapping projectors and cameras is presented, and extended to colorimetric calibration. In the case of projector out-of-focus blur due to oblique projection, an image preconditioning technique is proposed to compensate for the non-uniform blur.In an alternate approach, an analytical model for the oblique PSF is derived based on an apertured thin-lens model for the projector.In conclusion, some future directions for extending the work in this thesis are discussed, in conjunction with potential advancements in the capabilities of projector-camera systems.